Raja Haji Yahya in the History of 20th Century Malay Literature: (Raja Haji Yahya dalam Sejarah Kesusasteraan Melayu Abad ke-20) (Malay Literature, 2015)
Very little is known about the role of courtiers in the tradition of the Malay lipur lara (folklore) although the probability of them playing a role is hardly deniable. One such courtier is Raja Haji Yahya who lived in Chenderiang, Perak. Aside from producing works on the genealogy and history of the rulers of Perak, Raja Haji Yahya too was known to serve as penghulu (headman), pawang istana (royal medicine man), collector of folklore, and poet. In addition, he was well-acquainted with a prominent penglipur lara (folklorist) in Perak named Pawang Ana. This article aims to trace the life story of Raja Haji Yahya and discuss his contribution to the history of Malay literature in Perak. The study is based on several works of Raja Haji Yahya that have been found and also on information gathered from his next-of-kin who are still around today. The last part of the article puts forward a number of conclusions about the status of Raja Haji Yahya as a courtier who was blessed with deep insights into the literature and socio-cultural life of the Malays such that he deserves to be acknowledged as one of the leading lights in the history of Malay literature of 20th century Perak.Keywords: Raja Haji Yahya, history of Malay literature, Pawang Ana, folklorist, Perak